COMPARISON BETWEEN THE EFFECT OF THE COMMUNITY-BASED INTERACTIVE APPROACH AND THE INFLUENCE OF THE DISTRIBUTION OF BOOKLETS REGARDING THE SELF-MEDICATION KNOWLEDGE, ATTITUDE, AND BEHAVIOR OF STUDENTS - Untari, Eka Kartika; Supardi, Sudibyo; Sauriasari, Rani (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was conducted to compare the effectiveness of booklet media and a community-based interactive approach (CBIA) on non-medical science students. The study was conducted at the Departments of Pedagogy and Forestry at the University of Tanjungpura, Pontianak. Methods: The study design was pre-experimental with a pre- and post-test of the respondents, who were divided into groups that either carried out the CBIA or were given a booklet. There were 78 respondents who participated in the study until its completion. Scores of knowledge, behaviors, and attitudes were measured with questionnaires, both before and 6 weeks after interventions with the CBIA and the booklet. Results: The results demonstrate that both the CBIA and the booklet intervention significantly influence the level of knowledge, attitudes, and behaviors (p<0.05). Conclusions: Although the distribution of the booklets was more effective than the CBIA method in improving the self-medication attitude of the students, both interventions were equally effective in improving the self-medication knowledge and behavior of the non-medical science students.